The Transformation of Augmented Reality (AR) Technology Utilization in the Retail Industry: A Case Study of ZARA Online Store - Pelawi, Pioneer; Tulim, Anto; Siregar, Ekun Melki Mozart (JURNAL MANAJEMEN MOTIVASI, 2025)
This study investigates the implementation of Augmented Reality (AR) in enhancing customer experience and influencing purchase decisions in ZARA’s online fashion store. Using a quantitative approach and convenience sampling of 206 respondents, the findings reveal that Presence, Convenience, and Usefulness significantly affect purchase decisions, while Enjoyment does not. The regression model used is proven valid and reliable, explaining 64.2% of the variance. These results suggest that AR technology, particularly when focused on functionality and convenience, can effectively increase consumer engagement and purchase conversion in the fashion retail industry.